Entoloma fulvoviolaceum Noordel. & Vauras- not previously reported from Norway - Lorås, Jostein; Eidissen, Siw Elin; Weholt, Øyvind (Norges Sopp- og nyttevekstforbund, 2016)
- In the period 2009-2014 Entoloma fulvoviolaceum was found in at least five different locations in Holmvassdalen Nature Reserve in North Norway. The species was first described from Finland in 2003, and so far Holmvassdalen is the only place where it with certainty has been reported outside thetype locality. Details of macro- and icroscopical features and ecology are presented in the article.